Capacidade protetiva de novos isolados fracos de Citrus tristeza virus para utilização em programa de pré-imunização de laranja 'Pêra' - Zanutto, Carlos Alexandre (2009)
For the control of the damages induced by the Citrus tristeza virus (CTV), it was adopted the use of tolerant rootstock and the pre-immunization, which uses mild CTV isolates to protect against subsequent infections with severe isolates. Studies have demonstrated that selected mild isolates in the region of orchard are superior in their protective characteristics. In this perspective, 20 plants of elite 'Pêra' sweet orange, which have been standing out for their production and development were selected in the North and Northwest regions of the State of Paraná and subjected to the biological indexation and molecular tests for detection of virus, viroides and bacteria, responsible for the diseases in citrus. The protective value of the isolates of CTV of those plants was determined, in a first stage, through the molecular characterization by the RFLP analyses (restriction fragment length polymorphism) and SSCP (Single Strand Conformational Polymorphism) of the gene of the capsid protein, establishing comparisons between mild and severe isolates. In the next stage, those isolates potentially mild and protective, were subjected to challenge tests with the inoculation of severe isolate 'Rolândia' through the union of tissues (grafting) or through the vector 'Brown citrus aphid' (Toxoptera citricida Kirkaldy). The results showed that the selected plants presented potential to be used in pre-immunization programs, and biological indexation and the molecular characterization through RFLP and SSCP of the gene of the capsid protein indicated the presence of mild isolates of the virus. Among those isolates, some stood out, showing a better protective value, front to the challenge with the severe isolate, evidenced by SSCP analysis of the plants kept in greenhouse. The molecular analysis SSCP showed to be an excellent complementary tool to experiments of field performance, in order to monitor the stability of the viral complex presented in the plants. The evaluation of isolates through the SSCP analysis and in field experiment, showed the isolate number 1, collected in the Cruzeiro do Sul County (CS-1) as the most promising isolate to the protection of 'Pera' sweet orange on commercial orchards located in northern and northwestern of Paraná. The severe isolate of the CTV called Rolândia, showed itself stable and with high genetic divergence among the others severe isolates used (Capão Bonito and Barão B), as well as all the isolates tested.